Effect of zinc administration on the activities of some Zn- metallo enzymes in pre-ruminant buffalo calves - SINGH, CHARANBIR; SINGHA, S P S (The Indian Journal of Animal Sciences, 2014)
Effect of administration of zinc on the activities of some Zn-metalloenzymes, was investigated in blood and various tissues of pre-ruminant buffalo calves. Zinc administration caused higher plasma zinc levels and selective accumulation of zinc in liver and kidney. Zinc treated calves had significantly higher activities of plasma alkaline phosphatase (AP). carbonic anhydrase (CA) and super oxide dismutase (SOD) and these were positively correlated to increased plasma zinc levels. However, there was no Significant change in plasma LDH activities and these had no correlation with plasma Zn concentrations. AP, CA and SOD activities were significantly higher in liver and kidney only, because of their increased Zn levels. LDH activities were not correlated to the Zn concentrations of the tissues of both control and zinc treated groups. It was proposed that AP, CA and SOD were sensitive indicators of zinc status of the body while LDH activity had no correlation with the Zn concentration.